Evaluación de tres tipos de tuberías usadas en tratamientos magnéticos para reducción de concentraciones de calcio y magnesio en aguas duras. - Vera Saltos, Ronald Donald (2018)
The objective of the research was to evaluate three pipes of different material (copper, aluminum, PVC) that are used in magnetic treatment of hard water. The hard water used for the experimentation was from the well of the agroindustrial zone of the Polytechnic Superior School of Agriculture of Manabí that maintains averages of hardness of 350 mg / L. As a general sample, 7 liters were considered and a water pump of 40 L / min was required for recirculation. Each pipe was used for 5 minutes, with the magnetic technology consisting of two ceramic magnets of 1295.8 gauss each, arranged one on each side of the pipe by a plastic band; at 1 minute intervals samples were taken to perform the total hardness, calcium hardness and alkalinity tests. The pH and temperature of the hard water was examined at each interval where the pump was turned off to take the samples. The results dictated that the magnetic technology is effective to decrease the hardness of the water, but there was no noticeable difference in the material of the pipes used. Unlike the initial sample, which had no presence of carbonates, all samples had it. It was possible to determine that the temperature and the pH during the minutes had an increase, this due to the agitation of the water in the recirculation.